2002
DOI: 10.1124/jpet.102.035899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pyridine Ring Substitutions on Affinity, Efficacy, and Subtype Selectivity of Neuronal Nicotinic Receptor Agonist Epibatidine

Abstract: 2Ј-Pyridine ring substituted analogs of epibatidine were assessed for equilibrium binding affinity, functional potency, and efficacy at rat neuronal nicotinic receptors expressed in Xenopus oocytes. Binding affinities were determined in membrane homogenates from oocytes expressing ␣2␤2, ␣2␤4, ␣3␤2, ␣3␤4, ␣4␤2, or ␣4␤4. Efficacy (relative to acetylcholine) and potency were measured electrophysiologically with oocytes expressing ␣3␤4, ␣4␤2, and ␣4␤4. Hydroxy, dimethylamino, and trifluoromethanesulfonate analogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
(26 reference statements)
4
28
0
Order By: Relevance
“…because equilibrium binding and functional characterization reflect the affinity of the agonist for the desensitized and activated state of the nAChR, respectively, a clear-cut correlation between affinity and potency cannot be assumed. In agreement with this, very different findings on the correlation between binding and functional data have been reported from studies on epibatidine and cytisine analogs at various recombinant neuronal nAChRs (Avalos et al, 2002;Slater et al, 2003). In this study, we observed a clear correlation between binding and functional properties of the compounds at the ␣3␤4 nAChR (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…because equilibrium binding and functional characterization reflect the affinity of the agonist for the desensitized and activated state of the nAChR, respectively, a clear-cut correlation between affinity and potency cannot be assumed. In agreement with this, very different findings on the correlation between binding and functional data have been reported from studies on epibatidine and cytisine analogs at various recombinant neuronal nAChRs (Avalos et al, 2002;Slater et al, 2003). In this study, we observed a clear correlation between binding and functional properties of the compounds at the ␣3␤4 nAChR (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…As expected from previous studies with fluoro-and norchloro-analogues of epibatidine [116] , the newly-designed homoepibatidine analogues have 20-to 60-fold lower and 1.55 μg/kg for (+)-fl ubatine after i.v. injection [119] .…”
Section: Fig 2 Key Molecules For Development Of New Pet Radiotracersupporting
confidence: 82%
“…As expected from previous studies with fluoro-and norchloro-analogues of epibatidine [116] , the newly-designed homoepibatidine analogues have 20-to 60-fold lower affinities to ganglionic α3β4 nAChRs than to the α4β2 subtype [117] . For fl ubatine, the increase in subtype selectivity seemingly results in decreased pharmacological sideeffects compared to epibatidine.…”
Section: New Compoundssupporting
confidence: 81%
See 1 more Smart Citation
“…The binding affinity derived from this type of assay is primarily the affinity of the ligand for the desensitized state(s) of the receptor. Unfortunately, large differences in affinity observed in equilibrium binding assays are generally not observed in functional assays, and the rank order of affinities do not necessarily correlate with the rank orders of functional potency or efficacy (Avalos et al, 2002;Jensen et al, 2005). Thus, we find that the functional potency of varenicline at ␣4␤2, ␣3␤4, and ␣7 receptors varies by 24-fold or less.…”
Section: Downloaded Frommentioning
confidence: 79%